Approximation of First Grade MHD Squeezing Fluid Flow with Slip Boundary Condition Using DTM and OHAM. (30th May 2013) - Ullah, Inayat; Khan, Hamid; Rahim, M. T.
Abstract : A steady two-dimensional axisymmetric flow of an incompressible viscous fluid under the influence of a uniform transverse magnetic field with slip boundary condition is studied. An ordinary nonlinear differential equation is formed by transforming the Navier-Stokes equations using the transformation ψ ( r, z ) = r 2 G ( z ) . Differential transform and optimal homotopy analysis methods have been used to obtain the solutions by varying pertinent flow parameters. By using residuals in each case, the validity of solutions is established. Excellent results are obtained by using the proposed schemes. The influence of different parameters on the flow is shown through graphs.